The Mitochondrial Calcium Uniporter Interacts with Subunit c of the ATP Synthase of Trypanosomes and Humans - Huang, Guozhong (mBio, 2020)
Mitochondrial Ca(2+) transport mediated by the uniporter complex (MCUC) plays a key role in the regulation of cell bioenergetics in both trypanosomes and mammals. Here we report that Trypanosoma brucei MCU (TbMCU) subunits interact with subunit c of the mitochondrial ATP synthase (ATPc), as determined by coimmunoprecipitation and split-ubiquitin membrane-based yeast two-hybrid (MYTH) assays. Mutagenesis analysis in combination with MYTH assays suggested that transmembrane helices (TMHs) are determinants of this specific interaction. In situ tagging, followed by immunoprecipitation and immunofluorescence microscopy, revealed that T. brucei ATPc (TbATPc) coimmunoprecipitates with TbMCUC subunits and colocalizes with them to the mitochondria. Blue native PAGE and immunodetection analyses indicated that the TbMCUC is present together with the ATP synthase in a large protein complex with a molecular weight of approximately 900 kDa. Ablation of the TbMCUC subunits by RNA interference (RNAi) significantly increased the AMP/ATP ratio, revealing the downregulation of ATP production in the cells. Interestingly, the direct physical MCU-ATPc interaction is conserved in Trypanosoma cruzi and human cells. Specific interaction between human MCU (HsMCU) and human ATPc (HsATPc) was confirmed in vitro by mutagenesis and MYTH assays and in vivo by coimmunoprecipitation. In summary, our study has identified that MCU complex physically interacts with mitochondrial ATP synthase, possibly forming an MCUC-ATP megacomplex that couples ADP and P(i) transport with ATP synthesis, a process that is stimulated by Ca(2+) in trypanosomes and human cells.